# Negatieve exponent (reeks 2)

#### Zet om naar een positieve exponent

1. $$\left(\frac{-9}{7}\right)^{-2}$$
2. $$\left(\frac{-14}{3}\right)^{-1}$$
3. $$\left(\frac{-5}{4}\right)^{-4}$$
4. $$\left(\frac{-11}{3}\right)^{-2}$$
5. $$\left(\frac{-15}{8}\right)^{-2}$$
6. $$\left(\frac{-20}{3}\right)^{-2}$$
7. $$-\left(\frac{-4}{3}\right)^{-2}$$
8. $$-\left(\frac{-20}{7}\right)^{-2}$$
9. $$\left(\frac{-11}{5}\right)^{-3}$$
10. $$\left(\frac{-11}{7}\right)^{-3}$$
11. $$\left(\frac{-20}{3}\right)^{-4}$$
12. $$-\left(\frac{-9}{7}\right)^{-1}$$

#### Zet om naar een positieve exponent

##### Verbetersleutel

1. $$\left(\frac{-9}{7}\right)^{-2}=\left(-\frac{7}{9}\right)^{2}= \frac{7^{2}}{9^{2}}= \frac{49}{81}$$
2. $$\left(\frac{-14}{3}\right)^{-1}=\left(-\frac{3}{14}\right)^{1}=- \frac{3^{1}}{14^{1}}=- \frac{3}{14}$$
3. $$\left(\frac{-5}{4}\right)^{-4}=\left(-\frac{4}{5}\right)^{4}= \frac{4^{4}}{5^{4}}=\ldots \text{ZRM}$$
4. $$\left(\frac{-11}{3}\right)^{-2}=\left(-\frac{3}{11}\right)^{2}= \frac{3^{2}}{11^{2}}= \frac{9}{121}$$
5. $$\left(\frac{-15}{8}\right)^{-2}=\left(-\frac{8}{15}\right)^{2}= \frac{8^{2}}{15^{2}}= \frac{64}{225}$$
6. $$\left(\frac{-20}{3}\right)^{-2}=\left(-\frac{3}{20}\right)^{2}= \frac{3^{2}}{20^{2}}= \frac{9}{400}$$
7. $$-\left(\frac{-4}{3}\right)^{-2}=-\left(-\frac{3}{4}\right)^{2}=- \frac{3^{2}}{4^{2}}=- \frac{9}{16}$$
8. $$-\left(\frac{-20}{7}\right)^{-2}=-\left(-\frac{7}{20}\right)^{2}=- \frac{7^{2}}{20^{2}}=- \frac{49}{400}$$
9. $$\left(\frac{-11}{5}\right)^{-3}=\left(-\frac{5}{11}\right)^{3}=- \frac{5^{3}}{11^{3}}=\ldots \text{ZRM}$$
10. $$\left(\frac{-11}{7}\right)^{-3}=\left(-\frac{7}{11}\right)^{3}=- \frac{7^{3}}{11^{3}}=\ldots \text{ZRM}$$
11. $$\left(\frac{-20}{3}\right)^{-4}=\left(-\frac{3}{20}\right)^{4}= \frac{3^{4}}{20^{4}}=\ldots \text{ZRM}$$
12. $$-\left(\frac{-9}{7}\right)^{-1}=-\left(-\frac{7}{9}\right)^{1}= \frac{7^{1}}{9^{1}}= \frac{7}{9}$$
Oefeningengenerator vanhoeckes.be/wiskunde 2024-08-09 05:46:20